Global Epidemiology of Dengue Outbreaks in 1990–2015: A Systematic Review and Meta-Analysis - Guo, Congcong; Zhou, Zixing; Wen, Zihao; Liu, Yumei; Zeng, Chengli; Xiao, Di; Ou, Meiling; Han, Yajing; Huang, Shiqi; Liu, Dandan; Ye, Xiaohong; Zou, Xiaoqian; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Dengue is an arthropod-borne infectious disease caused by dengue virus (DENV) infection and transmitted by Aedes mosquitoes. Approximately 50–100 million people are infected with DENV each year, resulting in a high economic burden on both governments and individuals. Here, we conducted a systematic review and meta-analysis to summarize information regarding the epidemiology, clinical characteristics, and serotype distribution and risk factors for global dengue outbreaks occurring from 1990 to 2015. We searched the PubMed, Embase and Web of Science databases through December 2016 using the term “dengue outbreak.” In total, 3,853 studies were identified, of which 243 studies describing 262 dengue outbreaks met our inclusion criteria. The majority of outbreak-associated dengue cases were reported in the Western Pacific Region, particularly after the year 2010; these cases were primarily identified in China, Singapore and Malaysia. The pooled mean age of dengue-infected individuals was 30.1 years; of the included patients, 54.5% were male, 23.2% had DHF, 62.0% had secondary infections, and 1.3% died. The mean age of dengue patients reported after 2010 was older than that of patients reported before 2010 (34.0 vs. 27.2 years); however, the proportions of patients who had DHF, had secondary infections and died significantly decreased after 2010. Fever, malaise, headache, and asthenia were the most frequently reported clinical symptoms and signs among dengue patients. In addition, among the identified clinical symptoms and signs, positive tourniquet test (OR = 4.86), ascites (OR = 13.91) and shock (OR = 308.09) were identified as the best predictors of dengue infection, DHF and mortality, respectively (both P < 0.05). The main risk factors for dengue infection, DHF and mortality were living with uncovered water container (OR = 1.65), suffering from hypotension (OR = 6.18) and suffering from diabetes mellitus (OR = 2.53), respectively (all P < 0.05). The serotype distribution varied with time and across WHO regions. Overall, co-infections were reported in 47.7% of the evaluated outbreaks, and the highest pooled mortality rate (2.0%) was identified in DENV-2 dominated outbreaks. Our study emphasizes the necessity of implementing programs focused on targeted prevention, early identification, and effective treatment.